2021
DOI: 10.1101/2021.12.15.472735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing regulation of short-term memory by basal ganglia direct and indirect pathways that are coactive during behavior

Abstract: The basal ganglia direct and indirect pathways are viewed to mediate opposing functions in movement. However, this classic model is challenged by recent findings that both pathways are coactive during behavior. We examined the roles of direct (dSPNs) and indirect (iSPNs) pathway spiny projection neurons in a decision-making task with a short-term memory (STM) component. Optogenetic stimulation of cortical-input-defined dSPNs and iSPNs during STM oppositely biased upcoming licking choice, without affecting lick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Taken together with previous work, our findings may thus imply limits in the use of artificial activations in assessing striatal pathway function. Our results may also imply that DMS pathways would not necessarily display opposing correlates of movements 14 , 18 , 38 41 , but rather opposing correlates of a decision process 12 , 13 , 20 , 22 , 34 , 37 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Taken together with previous work, our findings may thus imply limits in the use of artificial activations in assessing striatal pathway function. Our results may also imply that DMS pathways would not necessarily display opposing correlates of movements 14 , 18 , 38 41 , but rather opposing correlates of a decision process 12 , 13 , 20 , 22 , 34 , 37 .…”
Section: Discussionmentioning
confidence: 74%
“…In support of this view, many influential studies have shown that pathway-specific activation of the striatum produces opposing behavioral biases 2 14 . For example, direct or indirect pathway activation oppositely influences locomotion 2 4 , 14 , licking 5 , 11 , 15 , left/right rotations 2 , 3 , 11 , 16 , repetition/cessation of activation-paired behaviors 6 8 , and left/right movements to report value-based decisions 9 , 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vector-valued error would likely appear as tunings to various motor and task variables in experimental animals (Requirement 2 ), especially in the phase before the animals are so overtrained their error is zero. Indeed, cells in the SNr (Fan et al, 2012;Barter et al, 2015;Tang et al, 2021) as well as the SNc (Howe and Dombeck, 2016;Dodson et al, 2016;Coddington and Dudman, 2018;Avvisati et al, 2022) respond to a plethora of behavioral and task variables.…”
Section: Discussionmentioning
confidence: 99%
“…A vector-valued error would likely appear as tunings to various motor and task variables in experimental animals ( Requirement 2 ), especially in the phase before the animals are so overtrained their error is zero. Indeed, cells in the SNr (Fan et al, 2012; Barter et al, 2015; Tang et al, 2021) as well as the SNc (Howe and Dombeck, 2016; Dodson et al, 2016; Coddington and Dudman, 2018; Avvisati et al, 2022) respond to a plethora of behavioral and task variables. We deliberately excluded the details of how this error may be computed in the brain, but we speculate at least three possible algorithmic ways in which it could appear: Bran region regions such as motor cortex or cerebellum could have a forward model of the world as well as the target, and thus, can directly compute the error and send it to the midbrain. The brain could be wired as a set of hierarchical control loops, in which each loop provides the target for the level below (as proposed by Yin, 2014).…”
Section: Discussionmentioning
confidence: 99%